(untitled) (Journal of Information Technologies in Education (ITE), 2009)
The article deals with the problems of competency approach implementation to the process of education content formation. The comparative analysis of European and Ukrainian experience of key competencies list discussion has done. Ukrainian perspectives of the competency approach integration to the content of education curricula are revealed.